2010
DOI: 10.1007/s11071-010-9879-z
|View full text |Cite
|
Sign up to set email alerts
|

Topological horseshoe analysis and the circuit implementation for a four-wing chaotic attractor

Abstract: The paper first analyzes a newly reported three-dimensional four-wing chaotic attractor, and observes all kinds of attractors, including periodic and chaotic, by numerical simulation. Then, the chaotic characteristic of the system is proved by investigating the existence of a topological horseshoe in it, based on the topological horseshoe theory. At last, an electronic circuit is designed to implement the chaotic system. The results of circuit experiment coincided well with those of numerical simulation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 27 publications
0
7
0
Order By: Relevance
“…In 2011, Wang et al investigated a four-wing chaotic attractor and demonstrated that there existed heteroclinic orbits [12]. The four-wing chaotic attractors in [11,12] all meet the four-wing standards proposed in [10].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…In 2011, Wang et al investigated a four-wing chaotic attractor and demonstrated that there existed heteroclinic orbits [12]. The four-wing chaotic attractors in [11,12] all meet the four-wing standards proposed in [10].…”
Section: Introductionmentioning
confidence: 99%
“…In 1976, Rossler conducted important work that rekindled the interest in three-dimensional (3D) dissipative dynamical systems [5]. Then, many Lorenz-like or Lorenzbased chaotic systems were proposed and investigated [6][7][8][9][10][11][12][13][14][15][16][17].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, the topological horseshoe lemma was proposed as a practical and useful computer-assisted proof method [16]. This theory has already been used to prove the existence of chaos in some integer-order systems, for example Dong et al proved its existence in typical 3D systems [17][18][19][20], Wang et al proved the chaos existence in hyperchaos system [21][22][23][24], Jia et al analyzed the existence of chaos in fractional order Lü chaotic systems [25][26][27][28].…”
Section: Introductionmentioning
confidence: 99%
“…Latterly, by using several simple results on topological horseshoes, Li presented a new method for seeking horseshoes in dynamical systems [19]. This method has been applied to some practical systems to verify the existence of chaos [12,20,21].…”
Section: Introductionmentioning
confidence: 99%